OVERSEAS EXPERIENCE OF SOCIAL CONSEQUENCES CONNECTED WITH SCIENTIFIC AND TECHNOLOGICAL DEVELOPMENT OF GLOBAL ECONOMY AT THE CURRENT STAGE - Natalia E. Khristolyubova; Elena А. Hudorenko (Вестник Российского экономического университета имени Г. В. Плеханова)
The mode of life and activity, the standard of life are determined by deficit of fundamental scientific information about trends, problems, necessary conditions and possibilities of using the overseas experience for managing social consequences of scientific-technological development of global economy at the current stage of Russia modernization. In this context studying the impact of science and technology on the standard of life and wellbeing of people is very important. The authors analyze overseas experience of researching social consequences of scientific-technological development of global economy in order to assess possibilities of fragmented or complex use of gained new knowledge to improve the standard of life and to conduct further fundamental, practical and forecast research connected with the most important phenomena of the mankind development.